Assessment of Groundwater Quality Based on Matter Element Extension Model. (27th September 2012) - Jing, Jin; Hui, Qian; Yu-Fei, Chen; Wen-Juan, Xi
Abstract : The basic theory and calculating processes of matter element extension method are discussed in detail. Mass balance simulation is used to study the changes of groundwater chemistry. Results show that calcite and dolomite are oversaturated, while gypsum, fluorite, and halite are unsaturated in the simulation path; so calcite precipitates, while gypsum, fluorite, halite, and dolomite dissolve. The changing tendency of Ca 2+ /Na + is apparent. Because of the dissolution and precipitation of minerals, the content of each ion changes. Parameters of groundwater are basically within the permissible limits and meet the requirement of drinking water standards. By comparing the evaluation results obtained from matter element extension method, osculating value method based on entropy weight, and principal component analysis method, it is proved that matter element extension is an effective and reasonable method for groundwater quality assessment. The converting tendency of groundwater quality is judged based on the extension indexes; this characteristic is unique of matter element extension method.